Pembangunan Pertanian di Provinsi Jawa Barat : Analisis Kebijakan fiskal : Analisis Kebijakan Fiskal - Baghas Budi Wicaksono; Rifka Audinasari (Jurnal Riset Ilmu Ekonomi, 2023)
This study aims to determine the effect of local government expenditure on agricultural affairs and direct expenditure on the productivity of the agricultural sector in the Regency/City of West Java Province. The data used in this study is secondary panel data containing 26 regencies/cities in West Java Province during 2010 to 2017. Researchers used the Panel Regression method to identify the model used. The results of the study indicate that government expenditure in the forestry, livestock and food crops sub-sectors as well as direct expenditure components which include goods, services and capital have a positive and significant impact on agricultural productivity. This is indicated by the t-statistic having a greater value than the t-table (p-value <0.05). The regression model also has BLUE criteria, namely homoscedasticity, non-multicollinearity, and normally distributed data. The policy implications that can be carried out on the research results are: (1) Expansive fiscal policy is needed to encourage the agricultural sector in regencys/cities in West Java, (2) Use the budget dynamically for regions that have a comparative advantage in each of the leading commodities. , and (3) the acceleration of industrial technology in agriculture is needed so that productivity can be greater or exponential.